The Importance of Leadership in Da'wah: A Case Study at KUIM - Basyirah Bt Narudin (Universiti Sains Islam Malaysia, 2022)
According to this research, the effectiveness level of da'wah activities is accordance to the effectiveness level of leadership, in organizing da'wah. This research is based on the fieldwork research on a group of 50 students from Islamic University College of Malaysia (IUCM). This research is proposed to identify the perceptions towards the need of leadership in da'wah as to make the da'wah effective. Interviews, questionnaires and reviewing relevant documents were the tools for data gathering. The findings indicate that the perceptions of respondents towards the effectiveness level of IUCM as a da'wah organization are parallel with their perceptions towards the effectiveness level of leadership in IUCM. Finally, the researcher concludes that it is important to conduct da'wah either through individual or da'wah institutions by strengthening the element of leadership in the self of da'i and in managing the da'wah successfully.